Evaluación de dos métodos de resincronización de celos sobre los porcentajes de preñez en vaconas mestizas - Moreira Villamar, Eduardo Fabricio (2012)
SUMMARY We evaluated the efficiency of two methods of resynchronization of jealousy on the pregnancy rate in crossbred heifers and compared among themselves and with the traditional method of mating (review with bull after IATF). We used two levels of hormones (1 mg estradiol benzoate) and 2.5 ml of a synthetic analog of gonadotropin-releasing hormone (GnRH) plus a control treatment with bull review after a fixed time artificial insemination (IATF). We used 10 replicates per treatment. The experiment lasted 12 weeks. Statistical evaluation was performed with the Principal Component Analysis and double-entry tables, the averages found were adjusted with the Student test at 5% probability of error. We found statistical differences between resynchronization of jealousy and reviewing with bull. In comparing the treatment of 1 mg estradiol benzoate versus taurus heifers with bulls review found a difference of 44.4 % vs 55.5 % respectively. We conclude that the way to obtain higher rates of pregnancy is by reviewing with bull after the first IATF. Furthermore, when analyzing the two treatments economically and with bull review, we conclude that review with bull after primary insemination has an Internal Rate of Return (TIR) 1.27 dollars, being the most profitable.